REPRESENTASI RELASI MAKNA TERHADAP TUTURAN PEMAIN MOBILE LEGENDS IN-GAME - Christina Octaviana Asnat Rofael; Tri Indrayanti (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2026)
This research was motivated by the growth of digital communication in online games, specifically Mobile Legends, which utilizes in-game chat features as a medium for communication among players. The researcher aims to examine the relationships of meaning that emerge in players’ discourse during gameplay. A qualitative descriptive method was employed in this study, grounded in Abdul Chaer’s theory of semantic relations. Player utterances from Mobile Legends, obtained through documentation of in-game chat screenshots, served as the research data source. The findings revealed the presence of semantic relations specifically synonyms, antonyms, and hyponyms used by players in their communication. Synonymic relationships were found in 24 data points, indicating the use of linguistic variations to expedite coordination among players. Antonymic relationships were found in 8 data points, illustrating conflicting game conditions and strategies. Hyponymic relationships were found in 7 data points, indicating the use of game-specific terminology. The research findings suggest that Mobile Legends players’ communication forms a distinctive digital language pattern that is concise, contextual, and influenced by the online gaming situation.